New and efficient enantioselective synthesis of both enantiomers of the calcium channel blocker bepridil - Mujahid, Mohammad; Subramanian, Jambu; Nalla, Viswanadh; Sasikumar, Murugesan; Kunte, Sunita Sharad; Muthukrishnan, Murugan (New Journal of Chemistry, 2017)
A concise and efficient enantioselective synthesis of both enantiomers of bepridil, a calcium channel blocker, is reported. Jacobsen's hydrolytic kinetic resolution method was utilized to resolve racemic 2-(isobutoxymethyl) oxirane. The incorporation of the succinimide moiety by the Mitsunobu reaction, which was investigated in detail, occurred without any loss of enantioselectivity. Using this strategy, both enantiomers of the target molecule were obtained in good yield and with high enantiopurity (ee > 99%).